1995
DOI: 10.1021/bi00050a027
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the mitochondrial permeability transition by cyclosporin A during long time frame experiments: relationship between pore opening and the activity of mitochondrial phospholipases

Abstract: Inhibition of the mitochondrial permeability transition pore by cyclosporin A or trifluoperazine is transient on the time scale of cell injury studies (hours). However, these agents act synergistically and produce long-lasting inhibition when used in combination. The cause of this synergism has been investigated from the perspective of the known action of trifluoperazine as an inhibitor of mitochondrial phospholipase A2. Free fatty acids, which are phospholipase reaction products, facilitate pore opening in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(149 citation statements)
references
References 52 publications
7
139
0
Order By: Relevance
“…When administered together, CSA (0.5 p M ) and TFP (30 pM) completely suppressed mitochondrial iron trapping in these preparations (Fig. 5), an observation consistent with other studies reporting synergistic effects of combined CSA/TFP treatment on MTP permeability (Broekemeier and Pfeiffer, 1995;Bernardi, 1996).…”
Section: Role Of Mtpsupporting
confidence: 90%
See 1 more Smart Citation
“…When administered together, CSA (0.5 p M ) and TFP (30 pM) completely suppressed mitochondrial iron trapping in these preparations (Fig. 5), an observation consistent with other studies reporting synergistic effects of combined CSA/TFP treatment on MTP permeability (Broekemeier and Pfeiffer, 1995;Bernardi, 1996).…”
Section: Role Of Mtpsupporting
confidence: 90%
“…CSA is thought to inhibit pore opening by interacting with, and displacing, cyclophilin M. The latter is a peptidyl-propyl-cis-trans-isomerase localized to the mitochondrial matrix that binds to the MTP and increases the probability that the channel is maintained in the open configuration. TFP is an amphipathic molecule that promotes pore closure by inducing mitochondrial membrane hyperpolarization (Broekemeier and Pfeiffer, 1995;Bernardi, 1996). Incubation with CSA (0.06-0.5 pM) or TFP (1-30 pM) alone significantly inhibited mitochondrial iron sequestration elicited by DA exposure or HO-1 transfection in a dose-dependent fashion.…”
Section: Role Of Mtpmentioning
confidence: 99%
“…It was found that CsA in combination with trifluoropyrasine (TFP), the inhibitor of phospholipase A 2 , inhibited the TNF-induced release of cytochrome c and apoptosis (Figures 2c and 3c). Neither CsA nor TFP were effective alone (this is in line with the temporary inhibition of PTP by CsA in isolated mitochondria and prolongation of the CsA effect by TFP (Broekemeier and Pfeiffer, 1995)). MeVal-CsA, a CsA analogue effective in PTP inhibition but ineffective in inhibition of calcineurin, also suppressed TNFinduced apoptosis (not shown) so a role of calcineurin, the major non-mitochondrial CsA target, could be excluded.…”
Section: Ptp Is Involved In the Oligomycin-sensitive Tnf-induced Apomentioning
confidence: 65%
“…Its lifetime is very short in biological materials, which restricts its action to the close vicinity (Ͻ0.1 m) of the photosensitizer (24). Although the membrane lipid phase is clearly involved in modulating the PT, possibly through surface potential effects (25,26), we tend to exclude that pore inactivation by HP photodynamic action is due to lipid peroxidation, which should rather promote the PT (1).…”
Section: Discussionmentioning
confidence: 99%